PEMAKNAAN MASKULINITAS: Kajian Sosiologis Tentang Pemaknaan Maskulinitas Laki-Laki Di Kota Surakarta - WIBOWO, AGUNG; PARTINI, PARTINI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Javanese culture provides understanding to the men in Surakarta, how to behave and to be a man. Man, as an individual, in showing off his identity of masculinity attempts to build self-image based on interaction space in which he resides. This research explained the interpretation of hegemonic masculinities in Surakarta as the part of gender-to-age category relation from symbolic interactionism perspective. This study aimed (1) to find out the interpretation of masculinities manifested in man symbol, attitude, and behavior, (2) the dimensions affecting masculinity interpretation, (3) the transition of masculinity interpretation. This research was designed as a qualitative research, based on single case of masculinity interpretation by man in Surakarta. The analysis unit in this research was man. Technique of collecting data employed was in-depth interview with interview and observation guide. The data validation was done using source triangulation. The result of research showed that masculinity interpretation manifested in man symbol, attitude, and behavior in Surakarta was not singular. The dynamic of masculinity interpretation in symbolic interactionism perspective indicated the dominant subjectivity, meaning that masculinity interpretation was highly dependent on subject and interaction space he was encountering. Javanese culture affected the masculinity interpretation. Hegemonic masculinity was manifested through Javanese Culture's masculinity construction maintained by media and state by emphasizing on patriarchic construction. Having girlfriend and marriage is the momentum of the man's life journey transitioning affecting the masculinity interpretation. The notmarried man's masculinity suggested that his masculinity was positioned as free individual, while the married one indicated the attachment of individual to the role and position of man as the head of household.